The potential of plant systems to break the HIV‐TB link. Issue 10 (18th July 2019) - Habibi, Peyman; Daniell, Henry; Soccol, Carlos Ricardo; Grossi‐de‐Sa, Maria Fatima
Summary: Tuberculosis (TB) and human immunodeficiency virus (HIV) can place a major burden on healthcare systems and constitute the main challenges of diagnostic and therapeutic programmes. Infection with HIV is the most common cause of Mycobacterium tuberculosis (Mtb), which can accelerate the risk of latent TB reactivation by 20‐fold. Similarly, TB is considered the most relevant factor predisposing individuals to HIV infection. Thus, both pathogens can augment one another in a synergetic manner, accelerating the failure of immunological functions and resulting in subsequent death in the absence of treatment. Synergistic approaches involving the treatment of HIV as a tool to combat TB and vice versa are thus required in regions with a high burden of HIV and TB infection. In this context, plant systems are considered a promising approach for combatting HIV and TB in a resource‐limited setting because plant‐made drugs can be produced efficiently and inexpensively in developing countries and could be shared by the available agricultural infrastructure without the expensive requirement needed for cold chain storage and transportation. Moreover, the use of natural products from medicinal plants can eliminate the concerns associated with antiretroviral therapy (ART) and anti‐TB therapy (ATT), including drug interactions, drug‐related toxicity and multidrug resistance. In this review, we highlight the potential of plant system as a promising approach for the production of relevant pharmaceuticals for HIV and TB treatment. However, in the cases of HIV and TB, none of the plant‐made pharmaceuticals have been approved for clinical use. Limitations in reaching these goals are discussed.